The study of the extended Higgs boson sector within 2HDM model - Obikhod, T.V.; Petrenko, E.A. (Вопросы атомной науки и техники, 2017)
Consideration of the latest experimental data on the searches for extended sector of Higgs bosons produced at the LHC at a center-of-mass energy of 13TeV, allows for computer modeling of the properties of supersymmetric particles within 2HDM model. The experimental restrictions on model parameters accounted in FeynHiggs code that is implemented in SusHi program, gave us the possibility to calculate the cross sections and branching fractions for three mechanisms of production and decay of Higgs bosons: 1) pp→H→ττ, 2) pp→A →Zh→llbb, 3) pp→H→ hh→bbττ at a center-of-mass energy of 14TeV. The considered computer modelling make it possible to draw conclusions about the need to take into account the b-associated production process of Higgs bosons for fermionic decay channel at large values of tanβ. Differential cross sections with respect to the Higgs transverse momentum pₜ and pseudorapidity η are calculated and the peculiarities of the kinematics of the Higgs boson decay products are recognized.